2013
DOI: 10.1007/s00266-013-0177-2
|View full text |Cite
|
Sign up to set email alerts
|

Facial Rejuvenation With Fine-Barbed Threads: The Simple Miz Lift

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 15 publications
2
41
0
2
Order By: Relevance
“…They reported that 69.6% of the surgeons were highly satisfied, 7.5% had good satisfaction, and 2.9% were poorly satisfied. Our results are consistent with these results . In a study by Savoia et al (2014), 33 (89%) out of 37 patients were satisfied with their surgery.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…They reported that 69.6% of the surgeons were highly satisfied, 7.5% had good satisfaction, and 2.9% were poorly satisfied. Our results are consistent with these results . In a study by Savoia et al (2014), 33 (89%) out of 37 patients were satisfied with their surgery.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with these results. 14 variation) was circa 91% and in the second group (high age variation) was reported to be about 86%, which are in line with the results of our study. 18 Lycka et al (2004) studied the satisfaction of patients after surgery and concluded that 56.5% of the patients had very high satisfaction, 27.7% had good satisfaction, and 2.4% had poor satisfaction with the surgery.…”
Section: Discussionsupporting
confidence: 93%
“…1,2 Recently, there has been a growing trend for patients to pursue minimally invasive treatments with reduced risk of side effects and downtime to correct wrinkles and laxity. 2,[6][7][8] However, some patients dislike the idea of insertion of nonabsorbable threads that remain permanently in the facial soft tissue. 4 The evolution of thread lifting techniques and their application in the field of aesthetic procedure is now in its third decade.…”
mentioning
confidence: 99%
“…However, to some elderly patients, thread lift alone is not sufficient to counteract facial soft tissue ptosis, and conventional therapy would be the choice. In addition, based on our thread lifting technique, we should make temporal incisions to complete the thread lift technique [6]. However, through the dissected plane via lateral SMASectomy, our combined technique does not require any additional incisions.…”
Section: Discussionmentioning
confidence: 99%